RESEARCH OF THE PROPERTIES OF RAW MATERIALS AND YARN FROM COTTON FIBERS COLLECTED BY DIFFERENT METHODS (European Journal of Interdisciplinary Research and Development, 2024)
The article presents the results of experiments conducted to study the quality indicators of machine- and hand-picked cotton fiber, semi-finished products and yarn.